Troubles with Reality and Order through the Imagination in a World of Disbelief and Disorder: Wallace Stevens and Supreme Fiction (Global Journal of Human-Social Science, 2020)
The voice of the intellect is a soft one, but it does not rest until it has gained a hearing." -Sigmund Freud There have been a lot of writers throughout history who praised or criticized the world's beauty and ways. They all had their ideas and advice for humanity. But America's most celebrated twentiethcentury poet Wallace Stevens did not just rain down his ideas in his writings but took them as his motto for life. And he called the sum of his ideas 'Supreme Fiction'. This Supreme Fiction, according to Stevens, is a supreme level of poetry that cleanses the mind and soul of its readers and reduces the hardships they have to face in real life. In other words, Supreme Fiction is Stevens' replacement for the idea of God. Deeply influenced by the Nietzschean idea of the 'Death of God', Stevens wants to create a replacement for God for people to find comfort in a world of disbelief and disorder in the twentieth century.
Keywords: Stevens; supreme fiction; reality; the imagination; Nietzsche; death of god; world; disorder; poetry; order